Automotive handbook. - Reif, Konrad (Robert Bosche GmbH, 2022)
This is the eleventh edition of the definitive automotive technology reference. The BOSCH handbook series on different automotive technologies has become one of the most definitive sets of reference books that automotive engineers have at their disposal.